P75 Clinical predictors of continuous positive airway pressure requirement in bronchiolitis. (16th November 2010) - Evans, J; Marlais, M; Abrahamson, E
Abstract : Background: Bronchiolitis is the commonest respiratory viral illness in infants with the potential for significant morbidity. There is growing evidence for the use of continuous positive airway pressure (CPAP) non-invasive ventilation in the most seriously affected of these children. Despite the increasing literature regarding the use of CPAP there are currently no studies which identify clinical predictors of requirement for CPAP using the UK bronchiolitis age limit of 12 months, leaving the decision to clinical judgement alone. Objective: To identify clinical factors in infants with bronchiolitis at the time of presentation to the emergency department, which might predict a requirement for CPAP following admission. Methods: Retrospective review of paediatric emergency department case notes was conducted on all bronchiolitis admissions to one tertiary paediatric emergency department in a 12-month period (April 2009–March 2010). Inclusion criteria consisted of a clinical diagnosis of bronchiolitis in those 12 months of age or under. Potential clinical predictors were identified through an extensive literature review. Data extraction of these predetermined potential clinical predictors was carried out and recorded for each case. Logistic regression was then conducted for each variable to identify statistically significant independent predictors of CPAP requirment. Results: During the study period 163 infants were admitted with acute bronchiolitis. Of the 163 infants admitted 28 (17%) received CPAP. The most significant predictors of CPAP requirement in those admitted were as follows: lower oxygen saturation (mean 92.7% vs 97.1%, p<0.001), oxygen requirement in the emergency department (89.3% vs 24.4%, p<0.001), lower weight at presentation (mean 4221 g vs 6668 g, p<0.001), higher capillary blood gas PaCO2 (mean 8.32 kPa vs 6.05 kPa, p<0.001) and higher capillary blood gas HCO3 - (mean 30.5 mmol/l vs 26.5 mmol/l, p<0.001). Conclusion: We have identified a number of clinical variables which may be assessed within the emergency department, each independently predictive of CPAP requirement in those who are admitted with bronchiolitis. These findings are of particular importance as an aid to clinical assessment of bronchiolitis severity. They are also likely to have a useful role in logistical management decisions, allowing early planning for non-invasive ventilation.